Quality Assessment of Commercial Sandcrete Blocks in Minna Metropolis, Niger State (Nigerian Journal of Technology, 2022)
The spate of building collapse across the country over the years has raised questions about the quality of building materials and the need to investigate their suitability for construction. Sandcrete blocks are of interest been the most popular masonry unit widely employed in construction of walling units for building structures, hoardings of construction sites and foundations, in Nigeria. The aim of this study is to assess the quality of commercial Sandcrete blocks produced in Minna metropolis, Niger State, for compliance with existing standards: Nigerian Industrial Standard and Nigerian Building Code. The research was appraised through field surveys methods, sampling and laboratory experiments conducted on sixteen (16) selected block factories in Minna metropolis. A total of eighty (80) nine-inch blocks, five (5) each, were sampled from each factory and subjected to dimensional checks, water absorption and compressive strength tests. The results obtained from the laboratory experiments showed that the dimension, compressive strength and water absorption capacity of the sampled blocks were below standard specifications. The highlight of the field survey carried out showed discrepancies in the mix proportioning, curing practices and age of blocks utilized in the factories against those of the standards. Consequently, it was recommended that blocks produced in Minna should never be used for load bearing walls.